The importance of ICT in creating digital marketing - Chomiak-Orsa, Iwona; Liszczyk, Konrad (Znaczenie ICT w kreowaniu marketingu cyfrowego, 2020)
The creation of digital marketing was conditioned by many experiences of using its previous forms, derived from interpersonal communication itself. The moment when society entered into interaction with new information and communication technologies forced a kind of integration of both issues, which began to create a new concept known today as digital marketing. Its key channels, including online technologies used to communicate with recipients, serve many businesses as a leading tool for promoting their own brand. The aim of the article is to illustrate the process of a marketing evolution towards its digital version through the presentation of the technologies used, as well as a step-by-step approach to online sales using methods from the borderline of ICT in image building and sales. It can be said without any doubt that marketing communication is evolving from classic solutions and interactions to its digitalized counterpart, which is mainly found in online solutions. The research method used in the article was a critical analysis of the literature and identification with the characteristics of information and communication solutions used to create digital marketing
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 1 (55), s. 9-20
Keywords: marketing; digital marketing; information and communication technologies; online technologies; sales relations; marketing cyfrowy; technologie informacyjno-komunikacyjne; technologie online; relacje sprzedażowe